Study of plasma formation in a planar type ion diode with self-magnetic isolation; Journal of Physics: Conference Series; Vol. 1115 : 6th International Congress "Energy Fluxes and Radiation Effects"/ 20th International Symposium on High-Current Electronics (20th SHCE) - Stepanov A. V. Andrey Vladimirovich (2018, 2018)
Title screen